2019
DOI: 10.1016/j.ceramint.2018.12.178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of yttrium doping on the structural, morphological and optical properties of nanostructured ZnO thin films grown by spray pyrolysis

Abstract: Influence of yttrium doping on the structural, morphological and optical properties of nanostructured ZnO thin films grown by spray pyrolysis, Ceramics International,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Yttrium (Y) is an environmentally-friendly and abundant rare earth (RE) element [21]. The radius of yttrium is close to the atomic radius of zinc (Zn), which facilitates the insertion of Y ions into the ZnO lattice [22]. So far, some studies on Y-doped ZnO have shown that impurity levels could be introduced in the forbidden band by Y doping, and the valence electron transition with low-energy excitation could improve the utilization of visible light [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Yttrium (Y) is an environmentally-friendly and abundant rare earth (RE) element [21]. The radius of yttrium is close to the atomic radius of zinc (Zn), which facilitates the insertion of Y ions into the ZnO lattice [22]. So far, some studies on Y-doped ZnO have shown that impurity levels could be introduced in the forbidden band by Y doping, and the valence electron transition with low-energy excitation could improve the utilization of visible light [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A prominent peak corresponding to (002) plane has been observed for all of our samples. No additional peaks due to segregated yttrium-rich phases have been found in any of the films under test, thus indicating their high phase homogeneity [7]. This also indicates that Y ions are uniformly substituted into either Zn sites or interstitial sites in the ZnO lattice.…”
Section: Resultsmentioning
confidence: 82%
“…Transparent conductive ZnO-based oxides are mainly obtained by doping with group-III elements such as In, Al, and Ga [2]. In spite of great potential practical and fundamental interest, the number of publications that deal with the properties of yttrium-doped zinc oxide films still remains insufficient [3][4][5][6][7]. For optimal application of ZnO:Y films, it is necessary to have indepth knowledge of their structure and optical and electrical properties.…”
Section: Effect Of Dopant Concentration and Crystalline Structure On The Absorption Edge In Zno:y Films 1 Introductionmentioning
confidence: 99%
“…Translucent oxides such as CuO, SnO 2 , and ZnO have invaded photovoltaic and detecting systems industrial sectors [1,2]. The inherited high excitation binding energy of ZnO [3], physical and chemical stability [4]. Based on these observed outstanding properties, ZnO has been widely used in the fabrication of photodetectors, reminiscence uses, LED,…”
Section: Introductionmentioning
confidence: 99%